2019
DOI: 10.1175/mwr-d-18-0199.1
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Optimization for Real-World ENSO Forecast in an Intermediate Coupled Model

Abstract: We performed parameter estimation in the Zebiak–Cane model for the real-world scenario using the approach of ensemble Kalman filter (EnKF) data assimilation and the observational data of sea surface temperature and wind stress analyses. With real-world data assimilation in the coupled model, our study shows that model parameters converge toward stable values. Furthermore, the new parameters improve the real-world ENSO prediction skill, with the skill improved most by the parameter of the highest climate sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
(41 reference statements)
1
8
1
Order By: Relevance
“…Here, we use NINO 3.4 (5°S to 5°N, 170–120°W) index to represent ENSO activities. In the control run, the model shows the roughly 4‐year ENSO periodicity through the lagged correlation and a distinct ENSO SPB feature (Figure S1), which is consistent with Zhao et al (2019).…”
Section: Methods Model and Datasupporting
confidence: 89%
See 2 more Smart Citations
“…Here, we use NINO 3.4 (5°S to 5°N, 170–120°W) index to represent ENSO activities. In the control run, the model shows the roughly 4‐year ENSO periodicity through the lagged correlation and a distinct ENSO SPB feature (Figure S1), which is consistent with Zhao et al (2019).…”
Section: Methods Model and Datasupporting
confidence: 89%
“…We use an intermediate coupled ocean‐atmosphere model—the latest version of Cane‐Zebiak model (Lamont‐Doherty Earth Observatory, Version 5, LDEO5; Chen et al, 2004; Zhao et al, 2019) to simulate the unstable ENSO mode. The atmospheric model is built on the steady‐state, linear shallow water equations, with the atmospheric circulation driven by a heating anomaly which consists of moisture convergence and SST anomalies.…”
Section: Methods Model and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al (2012) use an intermediate complexity coupled model to investigate a method which allows for a geographic-dependent parameter optimization, and find the geographic dependent technique superior to the single-value parameter estimation technique for both climate estimates and predictions. Recently, Zhao et al (2019) found that ensemble-based Kalman Filter parameter optimization in the Zebiak-Cane model (Zebiak & Cane, 1987) improves El Nino Southern Oscillation prediction skill. Other techniques for parameter estimation include Markov chain Monte Carlo algorithms (e.g., Posselt & Bishop, 2012), and gradient descent and genetic algorithms (e.g., Sumata et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, its prediction skill became comparable to the most advanced coupled general circulation models (CGCMs) after a bias-correction method was incorporated that reduced large systematic model biases (Chen et al 2000). This model has since become a benchmark for ENSO prediction models and has been intensively used in simulating and predicting ENSO in the past decades (Cheng et al 2010;Wu 2016;Peng et al 2018;Zhao et al 2019). Since its latest version LDEO5 was reported in the seminal paper by Chen et al (2004), this model-based prediction system has not been further developed.…”
Section: Introductionmentioning
confidence: 99%